Efficacy assessment of levetiracetam monotherapy in newly-diagnosed epilepsy in adults using epileptiform activity index - V. A. Karlov; A. B. Kozhokaru; P. N. Vlasov; A. S. Samoilov; Yu. D. Udalov (Эпилепсия и пароксизмальные состояния)
Abstract. Levetiracetam (LEV) is one of the most commonly prescribed antiepileptic drugs (AED). However, there were no studies on its efficacy and safety in terms of the correlation with epileptiform activity index (EAI) performed among the Russian population.Aim. To evaluate the efficacy and tolerability of LEV monotherapy in patients with newly-diagnosed epilepsy using epileptiform activity index (EAI) assessment.Materials and methods. The study included 107 patients (46 (43.0%) male and 61 (57.0%) female) with focal epilepsy (FE) (39.3%; n=42) or idiopathic generalized epilepsy (IGE) (60.7%; n=65). At each visit, video-electroencephalographic (video-EEG) monitoring was performed (baseline and in 1, 3, 6, and 12 months of the therapy). Therapeutic drug monitoring was performed at dose titration in 1 month of the therapy or in case of therapy correction. Treatment efficacy was assessed using the criteria of seizure absence (medically induced remission), seizure rate decrease by >50% (responders), seizure rate decrease by <50% – insufficient efficacy, a composite index of efficacy/tolerability (retention on treatment), and seizure rate increase compared to baseline and/or development of a new type of seizures (aggravation). Adverse events (AE) were assessed using the scale for side effects in AED treatment (SIDAED).Results. Total EAI at baseline was 5.2-fold higher in patients with IGE compared to FE patients (23.4±3.0 and 4.5±0.97, respectively). After 1 month of LEV therapy, EAI decreased to 3.4±1.1 and 1.9±0.4 in patients with IGE and FE, respectively (p<0.01). The decrease continued during the whole follow-up period. Retention on monotherapy was achieved in 82.2% (n=88/107) patients; in 87.6% (n=57/65) patients with IGE and in 73.8% (n=31/42) with FE. The rate of serious AEs during the follow-up period was 8.4% (n=9).Conclusions. LEV is an effective drug of choice for the initial treatment of newly-diagnosed FE and IGE in monotherapy along with a significant decrease in EAI. EAI is an objective measure of LEV treatment efficacy.